A Fluorescence Study on Surface Properties of Cationic Gemini Surfactant with Some Special Alcohols - RIYAJ MOHAMMAD (Borneo Journal of Resource Science and Technology, 2020)
Alcohols are very important additives and played a measure role as co-surfactants in various industrial and research applications. While, Gemini surfactants are mainly used as effective emulsifiers, antifoaming agents, bactericidal agents, coating agents and corrosion inhibitors etc. Therefore, it is important to study about the variations in alkanol concentrations which affects the aggregation number and other related parameters. Surface properties of gemini surfactant butanediyl-1,4-bis(dimethyldodecylammonium bromide) (12-4-12) has been studied by using fluorescence method. This method has been used to calculate the aggregation number (Nagg) and the other related parameters like dielectric constant (D), Stern Volmer binding constant (KSV) of mixed system. This method is also very important for the calculation of the micropolarity of the mixed system (gemini/alcohol). The micropolarity has been obtained with the help of the ratio of intensity of peaks (I1/I3) of the pyrene fluorescence emission spectrum. Cetylpridinium chloride and pyrene were used as quencher and probe, respectively. Keywords: Gemini surfactant, special alcohols, aggregation number, micropolarity